Three Phase Grid-Tied Single Stage Reconfigurable Solar Converter Controlled By SVPWM Technique (International Journal of Engineering and Computer Science, 2014)
This project addresses a dc/dc converter & dc/ac converter suitable for an energy storage system with an additional function of galvanic isolation. An energy storage device such as an electric double layer capacitor is directly This project addresses a dc/dc converter & dc/ac converter suitable for an energy storage system with an additional function of galvanic isolation. An energy storage device such as an electric double layer capacitor is directly linked to one of the dc buses of the dc/dc converter without any chopper circuit. Nevertheless, the dc/dc converter dc/ac converter can continue operating when the voltage across the energy storage device droops along with its discharge. Theoretical calculation and experimental measurement reveal that power loss and peak current impose limitations on a permissible dc-voltage range. In this project verifies that the dc/dc converter can charge and discharge the capacitor bank properly. Moreover, the dc/dc converter & dc/ac converter can charge the capacitor bank from zero to the rated voltage without any external pre charging circuit.In this project, a new converter called reconfigurable solar converter (RSC) for photovoltaic (PV)-battery application, mainly utility-scale PV-battery application is presented. The major notion of the new converter is to use a single-stage three phase grid-tie solar PV converter to perform dc/ac and dc/dc operations. This converter solution is urging for PV- battery application, since it reduces the number of conversion stages, thereby developing efficiency and reducing cost, weight, and volume. In this project, a combination of analysis and simulation tests is used to show the attractive performance features of the suggested RSC.